(untitled) (Journal of Economic Research & Business Administration, 2017)
The topic of this article is the rationale of the issue on the need to develop and implement a corporate governance system (CGS) in higher educational establishments in Kazakhstan. The main directions and idea of the article are concluded in the significance of such innovations in the university management structure under conditions of transformation into a new organizational and legal form of a noncommercial corporation (NCC). The scientific significance of the work is obtaining new knowledge about the regularitiesand connectionsin the issue of constructing the optimal structure in the management system of the university. The practical importance of the work lies in justifying the issue of implementing solutions and corporate governance. Also, it can become a guide for the implementation of the transformation processes in the university in the form of the NCC. So, for example, the result of practical application can be the introduction of the main provisions proposed in the article in the manuals, instructions and techniques for the effective development of the CGS. The methodological part of the work was provided mainly by studying and using the works of foreign scientists on the basics of corporate governance used in leading companies in the world. In addition, we used the research materials of authoritative analytical companies on the topic under study. As the main conclusion of the article obtained on the basis of the results of the study, it is necessary to emphasize the validity of the need for introduction of CGSin higher educational establishments of Kazakhstan, in particular, Al-Farabi KazNU.